CRITICAL PERIOD FOR CROP-WEED COMPETITION IN GROUNDNUT (Arachis hypogaea L.) UNDER WET SEASON IN THE NORTHERN GUINEA AND SUDAN SAVANNA OF NIGERIA - Ahmadu, I. S.; Muhammad, J.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Field experiment was conducted during 2019 wet season to determine the critical period of weed control and its effects on the crop growth, yields, and yield components of groundnut at the Institute for Agricultural Research (IAR) Farm Ahmadu Bello University, Samaru and the Irrigation Research Kadawa, Nigeria. Two series of treatments with six weed-free (WF) and weed-infested (WI) periods were employed in the study. From the emergence of groundnut to maturity, the plots were kept weed-free for 2, 4, 6, 8, 10 weeks after sowing (WAS) and weeds were allowed to grow until harvesting of the groundnut and vice-versa before weeding. The treatments were laid out in a Randomized Complete Block Design with 3 replications. The weed density and biomass, growth and yield attributes and yield were recorded. The result showed that weed free period did not significantly influence shelling %, 100-seed weight and stand count of groundnut. Total dry matter, plant height, canopy spread and leaf number per plan were observed to increase with removal of weeds but decreased with delay in removal of weeds. The depletion of resource by weed resulted in scarcity of resources and ultimately crop plants had less number of pod per plant, pod weight and seed yield per hectare. The highest percent weed accumulation, weed removal, pod yield loss and pod yield gain all were observed between 4 and 8 WAS, suggesting the period to be the stage that is critical to avoid competition with weeds. In conclusion, the critical weed removal for maximum yields was found to be 4 weeks, beginning 4 weeks after sowing and ending 8 weeks after sowing.